Karakteristik Pridadi Ideal Konselor Dalam Perspektif Budaya Bugis - Sitti Rahmi (JKI (Jurnal Konseling Indonesia), 2016)
The aims of this research is to get overview releted the characteristics of concept individual ideal councelor in perspective Bugis society. Because the scope of the comprehensive study focused on only one contained in the message or the Bugis community known as pappaseng (message).This value is the value of acca (skills) contained in pappaseng is one of the four qualities that must possess a leader.to achieve these objectives, this research using qualitative approach with data collection methods, analysis and interpretation follow the rules of hermeneutics Gadamer. While the data source get through the book. Silasa: Kumpulan Petuah Bugis-Makassar Karya A. Hasan Machmud based search source book, there is 5 pappaseng data that overview the characteristic from velue of skills. the fifth such data, there are eleven behavioral characteristics and then categorized into four characteristics, namely 1) Full of consideration, 2) Communication skills and problem solving, 3) Positive thinking and 4) steadfast in honesty. Suggestions for further research in order to explore further the local values that can be absorbed into the concept of personal characteristics ideal counselor typical Indonesian culture.